Managing complexity and Covid-19: Life, liberty and the pursuit of happiness - GHOSH, Aurobindo (Institutional Knowledge at Singapore Management University, 2022)
This book brings together insights and perspectives from leading medical, legal, and business professionals, as well as academics and other members of civil society, on the threats and opportunities to life during the COVID-19 pandemic. It provides a uniquely interdisciplinary perspective for policymakers, researchers, and medical professionals to assess the different practical strategies, and risk and crisis management processes available to them in addressing the very difficult choices with which they are presented and their implications. The book presents a framework for the different facets of strategic choices faced by policymakers between life and livelihood, and the challenges of protecting health versus reopening the economy. It also evaluates the intense challenges faced by frontline medical professionals and scientists during an unfolding catastrophe. Finally, the authors explore the societal and human elements of the pandemic and its impact on family dynamics, society, education, and business, including the technology, creative, entertainment, and leisure industries.